Spatial Filtering Effect on Circular and Rectangular Electrode in Electrodynamic Sensor - Mohd Riduwan, Ghazali; Wan Ismail, Ibrahim; Nasrul Salim, Pakheri; M.F, Rahmat; M.F, Jusof (2011)
This paper is focus on spatial filtering effect or frequency bandwidths characteristics in circular and rectangular electrode. This spatial filtering effect is the relationship between sensor size and the frequency bandwidth of transducer determine from frequency response obtained during which corresponds to a detectable particle. The sensing device was built from conductor and insulator materials that have the different size and shape. Three types of electrodes that commonly used were pin, quarter ring and ring shapes. This paper focuses on pin shape with variation of size for circular and rectangular shapes. Non-intrusive method was designed and applied to the both shapes to investigate the spatial filtering effect of the sensor.